Considering the potential unintended consequences of RateMDs: an exploratory study in one specialty - Pulkki, Kristina H; Pira, Shamira; Young, Meredith; Scott, Grace M; Nhan, Carol; Fung, Kevin; Le Blanc, Gabriella; Nguyen, Lily HP (Canadian Medical Education Journal, 2025)
Background: Websites that facilitate communication between patients regarding their experiences with individual physicians are now relatively commonplace. Given patient-generated ratings are publicly available, physicians could use these to access rarely available patient feedback. We explored the content of reviews associated with low physician ratings and consider the potential benefits and consequences of relying on this form of freely available data to support individual life-long learning. Methods: We conducted an exploratory qualitative descriptive study. We collected narrative comments associated with low numerical ratings on one physician-rating website (RateMDs) drawn from one specialty in Canada. Written reviews associated with low numerical ratings (≤2/5) for Canadian otolaryngologists were collected yielding a total of 878 comment sets that were analyzed deductively and iteratively. Results: We found that patient comments described poor performance in areas that aligned, for the most part, with the CanMEDS roles including Professional, Communicator, and Leader; specifically referring to management of the clinical environment, administrative staff, and trainees. Conclusion: While not intended for physician feedback, physicians could access patient-to-patient ratings and associated written reviews as a means to identify areas of practice improvement. However, this represents an unintended use of these websites. While speculative, access to patient-to-patient rating websites could negatively impact physician confidence or self-worth – representing a negative consequence of their use. The utilization of these data for potential self-improvement represents an unintended use of patient-to-patient ratings and so may be accompanied by unintended consequences for physicians who use these data as potential feedback, and patients who contribute to physician rating sites.